2020
DOI: 10.1186/s12890-020-01199-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 1.1 mm flexible cryoprobe with conventional guide sheath and therapeutic bronchoscope in biopsy of apical upper lobe solitary pulmonary nodule

Abstract: Background: Lung cancer is frequently situated peripherally in the upper lobes of the lung. Acquiring adequate tissue from this difficult-to-reach area remains a challenge. Transbronchial cryobiopsy (TBCB) has the ability to acquire larger specimens, but the rigidity of the standard 1.9 mm and 2.4 mm cryoprobes frequently poses challenges when used with a guide sheath (GS). The novel 1.1 mm cryoprobe, being both smaller and more flexible, may address this limitation. We describe the usage of this 1.1 mm flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
(24 reference statements)
2
15
0
1
Order By: Relevance
“…A few studies reported the complications and the incidence in bronchoscopy [2,[9][10][11][12] . According to a study of 20,986 bronchoscopies [4] , the most common complications were hemorrhage, oxyhemoglobin desaturation, pneumothorax, and pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported the complications and the incidence in bronchoscopy [2,[9][10][11][12] . According to a study of 20,986 bronchoscopies [4] , the most common complications were hemorrhage, oxyhemoglobin desaturation, pneumothorax, and pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%
“…An ultrathin 1.1-mm cryoprobe, which is used through the working channel of an ultrathin bronchoscope, has already been adopted in clinics worldwide. The ultrathin cryoprobe is flexible enough to access PPLs located past the deepcurved bronchus (51) of a small sample size. Bronchoscope manufacturers have continued efforts to develop thinner bronchoscopes with larger working channels and better visibility.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…15,16 In recent years, a novel 1.1 mm cryoprobe, which can pass through the 1.7 mm working channel of a BF-MP 290F, became available in clinical settings, and therefore it is expected that large specimens can even be collected with an ultrathin bronchoscope. 17 It is also important to consider trying another sampling method, such as EBUS-TBNA, CTNB and surgical biopsy, if the specimen obtained from EBB/TBB is not appropriate for NGS analysis. 7,8,10 There were several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%